Integrating 3D Printing Technologies into Architectural Education as Design Tools - Boumaraf, Hemza; İnceoğlu, Mehmet (Ital Publication, 2020)
3D printing technology offers the chance to produce very small-scale, complex forms that could help to improve educational materials for architectural design. In this age of technological advances, architectural education needs to integrate modern teaching methods that could enhance students’ visual perception. This research thus examined the impact of computational design modeling and 3D printing technology on the spatial cognition of architecture students. It starts with the premise that the use of the 3D printed models will support design logic and improve the deep understanding of spatial perception among students. Thirty architecture students were asked about a designed project realized for the purpose of this study. They were presented both a project designed via computer modeling software and a printed model of the same project. The outcomes indicate that the use of 3D printing gave better results in the development of students’ spatial abilities. The findings also confirm that adopting this technology in the development of teaching tools will enhance students’ spatial perception and extend beyond the seamless materialization of the digital model which can continuously inform design ideation through emerging perception qualities.